Training Systems Using Python Statistical Modeling Explore Popular Techniques for Modeling Your Data in Python. - Miller, Curtis (Packt Publishing, Limited, 2019)
This book will acquaint you with various aspects of statistical analysis in Python. You will work with different types of prediction models, such as decision trees, random forests and neural networks. By the end of this book, you will be confident in using various Python packages to train your own models for effective machine learning.